An Antecedent-Outcome Model Of Responsible Innovation: A Resource-Based Perspective - Rasheed, Memon Khalid (2023)
ABSTRACT Firms are not built in an isolated world, nor can they survive without societal acceptance. Firms are responsible for their actions and innovations, even if those innovations are meant to be "social innovations." Increased awareness of economic and non-economic stakeholders has forced firms to seek social and ethical acceptability to be considered socially and cognitively desirable. It’s no longer about gaining profits only. Firms now need to address the rising concerns regarding upcoming technological innovations, especially artificially intelligent machines. Such technological innovations have serious impacts on human autonomy, fairness, justice, and agency. Collective and responsible stewardship based on some values and principles, through public engagement and informed discourse, may resolve such issues. The research proposes "responsible innovation" (RI) as the solution to all these problems. RI is a novel approach for managing technological innovations that makes the firm ethically, morally, and socially responsible, environmentally friendly, and humanitarian in addition to being business-oriented. Building on the resourcebased view, this study proposes and empirically tests RI as a distinctive competency of the firm developed as a result of its resources (tangible and intangible) and capabilities, leading towards sustainable competitive advantage (SCA) through the contingency effect of absorptive capacity, whereas higher sustainability performance (financial, social, and environmental) became the end result of the SCA gained.